Badass : ultimate deathmatch : skull-crushing true stories of the most hardcore showdowns, fistfights, last stands, suicide charges, and military engagements of all time /: ultimate deathmatch : skull-crushing true stories of the most hardcore showdowns, fistfights, last stands, suicide charges, and military engagements of all time. (2013) - Unknown
No abstract available